1994
DOI: 10.1080/00207149408409361
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Role of Source Misattributions in the Creation of False Beliefs Among Preschoolers

Abstract: In this article the authors examine one possible factor in the creation of false beliefs among preschool-aged children, namely, source misattributions. The authors present the results from an ongoing program of research which suggest that source misattributions could be a mechanism underlying children's false beliefs about having experienced fictitious events. Findings from this program of research indicate that, although all children are susceptible to making source misattributions, very young children may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
196
3
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 322 publications
(210 citation statements)
references
References 11 publications
9
196
3
2
Order By: Relevance
“…If children are exposed to misinformation during repeated interviews, young children in particular may incorporate the false verbatim information into their immediate memory accounts, thereby increasing inaccuracies (e.g., Brainerd & Reyna, 1990. Finally, when interviews are repeated, children may assume that their earlier responses were incorrect, leading to inaccuracies over time due to social pressure (e.g., Siegal, Waters, & Dinwiddy, 1988).Several studies confirm these possibilities and reveal remarkably high error rates among children exposed to repeated interviews about fictitious events (e. Ceci, Loftus, Leichtman, & Bruck, 1994). Leichtman and Ceci (1995), for instance, questioned preschool-age children on multiple occasions about a man's visit to their class.…”
supporting
confidence: 53%
“…If children are exposed to misinformation during repeated interviews, young children in particular may incorporate the false verbatim information into their immediate memory accounts, thereby increasing inaccuracies (e.g., Brainerd & Reyna, 1990. Finally, when interviews are repeated, children may assume that their earlier responses were incorrect, leading to inaccuracies over time due to social pressure (e.g., Siegal, Waters, & Dinwiddy, 1988).Several studies confirm these possibilities and reveal remarkably high error rates among children exposed to repeated interviews about fictitious events (e. Ceci, Loftus, Leichtman, & Bruck, 1994). Leichtman and Ceci (1995), for instance, questioned preschool-age children on multiple occasions about a man's visit to their class.…”
supporting
confidence: 53%
“…For example, children may need to distinguish between actions carried out on multiple occasions by the same perpetrator. Also, false accusations may occur because children imagine suggested but fictitious actions by a person and later mistakenly believe that those actions were actually carried out by that person (e.g., Ceci, Loftus, Leichtman, & Bruck, 1994). The similarity effect can be useful when Accumulating evidence, however, shows that difficulty discriminating between similar sources is not the sole reason for developmental differences in source monitoring.…”
Section: The Similarity Issuementioning
confidence: 99%
“…Accurate source identification often involves more strategic decision making and it is possible that children have a tendency to report the information that they remember without recalling its source or engaging in a more intensive and strategic analysis of its source. Second, although children's reports about actual and fictitious events sometimes do differ qualitatively (e.g., Alonso-Quecuty, 1995;Santtila, Roppola, & Niemi, 1999;Roberts, Lamb, Zale, & Randall, 1998), in some circumstances (e.g., after repeated, suggestive interviews) children's true and false reports are often qualitatively indistinguishable even by those with extensive experience with children's reports (e.g., Ceci et al, 1994). Hence, research on helping children to strategically reduce their own source errors may help improve the accuracy of their testimony.…”
Section: Interviewing Protocolsmentioning
confidence: 99%
“…As pointed out by Ceci, Loftus, Leichtman, and Bruck (1994) and Strange, Sutherland, and Garry (2006), past research has shown mixed results regarding this variable; sometimes repeated interviewing over time causes an increase, decrease, or no change in false memory recall. Factors such as participant age, years since alleged false memory, and amount of time delay may help explain why false memory recall increases and decreases over time.…”
Section: Memory Changes Over Timementioning
confidence: 99%